Portal Blood Flow Of Femgle Growing and Lactating Goats on Different Food Intakes - Djokowoerjo Sastradipradja; Dewi Apri Astuti; Harnowo Permadi; Pursani paridjo (Media Veteriner, 1997)
Net production or uptake rates of the portal drained viscera (PDV) were estimated by measuring portal venous blood flow (PBF) according to the Fidc principle in asmiation with measurement of arterio-venous blood concentration differences. H-paro-aminohippuric acid wes constantly infused into a mesenteric vein to measure PBF on female growing and lactating PE goats fed different levels of feed intakes. Cardiac output (CO) and whole body energy expenditure were measured by the carbondioxidee entry rate technique (CERT). PBF (n=2 for each group) of growing goats were 1032,624,652,486 and 394 mllmin for 100,90, 80,70 and60 % of ad libitum feeding which corresponded to 32.7, 17.4, 19.8, 14.8 and 13.7 % of CO. For lactating goats, PBF (n-2 each) were 500, 371 and 223 ml/min for 100, 90 and 80 % of ad libitum feeding, corresponding to 13.6, 13.7 atid 7.6 % of CO. The calorigenic effect associated with feed intake of growing goats varied in descending order from 45 to 20 % of total body energy expenditure, while that of lactrrting goats was around 7 %. Absorption of volatile fatty acids was proportional to level of dietary intake.